Physiological adaptations of motor units to endurance and strength training - Mrówczyński, Włodzimierz; Łochyński, Dawid (Akademia Wychowania Fizycznego w Poznaniu)
The motor units consisting of motoneuron and muscle fibers, is the smallest functional unit of the neuromuscular system, which has ability to adopt plastically to acting stimuli. The increase of the physical activity, evoked by various type of trainings is one of the most important factors which induces morphological, biochemical and physiological changes in motor units. Endurance and strength training are two forms of physical activity leading to differential modifications in physiological features of motor units. Endurance training improves ability of muscle to sustain contractile activity for a long time, while strength training improves muscle strength and power. This manuscript summarizes the knowledge on the essential physiological adaptations in the both components of motor units – motoneuron and muscle fibers to endurance and strength training. The main aim of this paper is to enhance understanding on the strategy by which the neuromuscular system optimizes its activity in order to improve capabilities of the skeletal muscles to both forms of physiological activity
Keywords: endurance training; strength training; motoneuron; motor units